A two‐wave study on the effects of cognitive demands of flexible work on cognitive flexibility, work engagement and fatigue. Issue 2 (10th May 2022) - Uhlig, Lars; Korunka, Christian; Prem, Roman; Kubicek, Bettina
Abstract: Cognitive demands of flexible work are the specific cognitive demands of planning of working times, planning of working places, structuring of work tasks and coordinating with others that arise from flexible work organisation. Although these demands have become increasingly widespread, their consequences are not well understood. We propose that cognitive demands of flexible work are challenge stressors that can benefit employees, by adding to their cognitive flexibility and work engagement, but also impair employees by causing fatigue. Hypotheses were tested using a two‐wave study design in a sample that recently switched to a more flexible work organisation ( N  = 279). Data were analysed using structural equation modelling. We found that planning of working times and planning of working places were related to increases in cognitive flexibility, and coordinating with others was related to increases in work engagement. No significant relations with fatigue were found. Thus, the results suggest that cognitive demands of flexible work helped employees to personally develop and feel motivated at work. However, effects on work engagement were rather small. Future research should control potential confounding variables more thoroughly and examine effects on short‐term strain outcomes.